A green, economical synthesis of β-ketonitriles and trifunctionalized building blocks from esters and lactones - Pienaar, Daniel P.; Butsi, Kamogelo R.; Rousseau, Amanda L.; Brady, Dean (Beilstein Journal of Organic Chemistry, 2019)
The acylation of the acetonitrile anion with lactones and esters in ethereal solvents was successfully exploited using inexpensive KOt-Bu to obtain a variety of β-ketonitriles and trifunctionalized building blocks, including useful O-unprotected diols. It was discovered that lactones react to produce the corresponding derivatized cyclic hemiketals. Furthermore, the addition of a catalytic amount of isopropanol, or 18-crown-6, was necessary to facilitate the reaction and to reduce side-product formation under ambient conditions.
Keywords: acylation; β-ketonitrile; enolizable; trifunctionalized; sustainable

(untitled) - Kiyokawa, K.; Nagata, T.; Minakata, S. (Synthesis, 2018)

(untitled) - Long, R. S. (J. Am. Chem. Soc., 1947)

(untitled) - Dorsch, J. B.; McElvain, S. M. (J. Am. Chem. Soc., 1932)

(untitled) - Levine, R.; Hauser, C. R. (J. Am. Chem. Soc., 1946)

(untitled) - Eby, C. J.; Hauser, C. R. (J. Am. Chem. Soc., 1957)

Bretherick's Handbook of Reactive Chemical Hazards - Urben, P. G.; Pitt, M. J. (Academic Press, 2007)

(untitled) - Mamuye, A. D.; Castoldi, L.; Azzena, U.; Holzer, W.; Pace, V. (Org. Biomol. Chem., 2015)

(untitled) - Miyamoto, Y.; Banno, Y.; Yamashita, T.; Fujimoto, T.; Oi, S.; Moritoh, Y.; Asakawa, T.; Kataoka, O.; Yashiro, H.; Takeuchi, K.; Suzuki, N.; Ikedo, K.; et al. (J. Med. Chem., 2011)

(untitled) - Ji, Y.; Trenkle, W. C.; Vowles, J. V. (Org. Lett., 2006)

(untitled) - Kim, B. R.; Lee, H.-G.; Kang, S.-B.; Jung, K.-J.; Sung, G. H.; Kim, J.-J.; Lee, S.-G.; Yoon, Y.-J. (Tetrahedron, 2013)

(untitled) - Sheldon, R. A. (Green Chem., 2017)

(untitled) - Clarke, C. J.; Tu, W.-C.; Levers, O.; Bröhl, A.; Hallett, J. P. (Chem. Rev., 2018)

(untitled) - Richard, J. P.; Williams, G.; Gao, J. (J. Am. Chem. Soc., 1999)

(untitled) - Fleming, F. F.; Zhang, Z.; Liu, W.; Knochel, P. (J. Org. Chem., 2005)

(untitled) - Fleming, F. F.; Shook, B. C. (Tetrahedron, 2002)

(untitled) - Cook, F. L.; Bowers, C. W.; Liotta, C. L. (J. Org. Chem., 1974)

Monosaccharides – Their Chemistry and Their Roles in Natural Products - Collins, P.; Ferrier, R. (John Wiley & Sons Ltd., 1995)

(untitled) - Liu, B.; Liu, M.; Xin, Z.; Zhao, H.; Serby, M. D.; Kosogof, C.; Nelson, L. T. J.; Szczepankiewicz, B. G.; Kaszubska, W.; Schaefer, V. G.; Falls, H. D.; Lin, C. W.; et al. (Bioorg. Med. Chem. Lett., 2006)
See for an example.

(untitled) - Hammond, R. J.; Poston, B. W.; Ghiviriga, I.; Feske, B. D. (Tetrahedron Lett., 2007)

(untitled) - Swellem, R. H.; Allam, Y. A.; Nawwar, G. A. M. (Z. Naturforsch., B: J. Chem. Sci., 1999)

(untitled) - Rimoldi, I.; Facchetti, G.; Nava, D.; Contente, M. L.; Gandolfi, R. (Tetrahedron: Asymmetry, 2016)

(untitled) - Wang, G.; Liu, X.; Zhao, G. (Tetrahedron: Asymmetry, 2005)